2019
DOI: 10.13057/biodiv/d200737
|View full text |Cite
|
Sign up to set email alerts
|

Detection of transovarial transmission of dengue virus in Aedes spp. (Diptera: Culicidae) from Brontokusuman Village, Yogyakarta, Indonesia

Abstract: Abstract. Windyaraini DH, Marsifah T, Mustangin Y, Poerwanto SH. 2019. Detection of transovarial transmission of dengue virus in Aedes spp. (Diptera: Culicidae) from Brontokusuman Village, Yogyakarta, Indonesia. Biodiversitas 20: 2061-2067. Dengue Hemorrhagic Fever (DHF) is an infectious vector-borne disease. It is caused by dengue virus infection through the vector of Aedes spp. Dengue virus can be transmitted transovarially from infected female mosquitoes to their eggs. The presence of transovarial transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
1
2
0
1
Order By: Relevance
“…With 78,300 inhabitants, this district is the most populous in the city [ 10 ]. The finding of transovarial transmission in this study confirms the previous opinion which stated that female mosquitoes infected with dengue virus in their ovaries can transmit the virus to their offspring transovarially [ 7 , 11 ]. However, only a small number of studies have used transovarial transmission and monitoring of viral vectors as tools for control and surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…With 78,300 inhabitants, this district is the most populous in the city [ 10 ]. The finding of transovarial transmission in this study confirms the previous opinion which stated that female mosquitoes infected with dengue virus in their ovaries can transmit the virus to their offspring transovarially [ 7 , 11 ]. However, only a small number of studies have used transovarial transmission and monitoring of viral vectors as tools for control and surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…It takes 3–8 days before the mosquito become capable of transmitting the virus ( Alto & Bettinardi, 2013 ; Carrington & Simmons, 2014 ) either vertically (transovarial) or horizontally. Vertical or transovarial transmission involves the passage of dengue viruses to the offspring through the eggs of infected female mosquitoes ( Wan Najdah et al., 2021 ; Windyaraini et al., 2019 ; da Costa et al., 2017 ; Joshi et al., 2002 ) while horizontal transmission involves the passage of dengue viruses to a vertebrate host via a vector. Typically, 4 days after being bitten by an infected Aedes mosquito, a person will develop viremia, a condition in which there is a high level of the dengue virus in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…Although not yet empirical in Bandar Lampung, several studies have reported transovariums in several cities in Indonesia. Transovary or vertical transmission is the entry of the dengue virus into the mosquito's ovary, so that the eggs that hatch already have the same virus as their parents (Tri Baskoro T. Satoto, Umniyati, Suardipa, & Sintorini, 2013;Tri Baskoro Tunggul Satoto et al, 2014;Wanti, Sila, Irfan, & Sinaga, 2016;Windyaraini, Marsifah, Mustangin, & Soenarwan Hery Poerwanto, 2019).…”
Section: Resultsmentioning
confidence: 99%